Respuesta :
distance formula : sqrt ((x2 - x1)^2 + (y2 - y1)^2)
(-4,5).....x1 = -4 and y1 = 5
(3,-2).....x2 = 3 and y2 = -2
time to sub and solve....
d = sqrt ((3 - (-4)^2 + (-2 - 5)^2)
d = sqrt ((3 + 4)^2 + (-7^2))
d = sqrt (7^2 + (-7^2)
d = sqrt (49 + 49)
d = sqrt 98
d = 9.899 rounds to 9.90 <===
(-4,5).....x1 = -4 and y1 = 5
(3,-2).....x2 = 3 and y2 = -2
time to sub and solve....
d = sqrt ((3 - (-4)^2 + (-2 - 5)^2)
d = sqrt ((3 + 4)^2 + (-7^2))
d = sqrt (7^2 + (-7^2)
d = sqrt (49 + 49)
d = sqrt 98
d = 9.899 rounds to 9.90 <===